Regulation of p53 in NIH3T3 mouse fibroblasts following hyperosmotic stress. Issue 6 (8th June 2015) - Lambert, Ian Henry; Enghoff, Maria Stine; Brandi, Marie‐Luise; Hoffmann, Else Kay
Abstract: The aim of this project was to analyze the regulation of p53 expression in NIH3T3 fibroblasts under the influence of increasing hyperosmotic stress. Expression of p53 showed a biphasic response pattern in NIH3T3 cells under increasing osmotic stress (337 mOsm to 737 mOsm) with a maximum at 587 mOsm. Under isotonic conditions p53 expression increased after addition of the proteasome inhibitor MG132 indicating that cellular p53 levels in unperturbed cells is kept low by proteasomal degradation. However, under hypertonic conditions p53 synthesis as well as p53 degradation were significantly reduced and it is demonstrated that the increase in p53 expression observed when tonicity is increased from 337 to 587 mOsm reflects that degradation is more inhibited than synthesis, whereas the decrease in p53 expression at higher tonicities reflects that synthesis is more inhibited than degradation. The activity of the p53 regulating proteins p38 MAP kinase and the ubiquitin ligase MDM2 were studied as a function of increasing osmolarity. MDM2 protein expression was unchanged at all osmolarities, whereas MDM2 phosphorylation (Ser 166 ) increased at osmolarities up to 537 mOsm and remained constant at higher osmolarities. Phosphorylation of p38 increased at osmolarities up to 687 mOsm which correlated with an increased phosphorylation of p53 (Ser 15 ) and the decreased p53 degradation. Caspase‐3 activity increased gradually with hypertonicity and at 737 mOsm both Caspase‐3 activity and annexin V binding are high even though p53 expression and activity are low, indicating that initiation of apoptosis under severe hypertonic conditions is not strictly controlled by p53. Abstract : Under isotonic conditions synthesis and degradation of p53 are both high and similar in size, which results in low p53 expression. Increasing the extracellular tonicity from isotonic 337 to 737 mOsm results in p53 phosphorylation, a decrease in degradation as well as synthesis of p53. At 587 mOsm the p53 synthesis exceeds its degradation significantly, which is reflected in high p53 protein expression.